2014
DOI: 10.1080/02602938.2014.890695
|View full text |Cite
|
Sign up to set email alerts
|

Online student evaluations of teaching: what are we sacrificing for the affordances of technology?

Abstract: In the context of increased emphasis on quality assurance of teaching, it is crucial that student evaluation of teaching (SET) methods are both reliable and workable in practice. Especially, online SET tends to raise criticisms with those most reactive to mechanisms of teaching accountability. However, most studies have been conducted with convenience, small and cross-sectional samples. Longitudinal studies are rare, as comparison studies on SET methodological approaches are generally pilot studies followed sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…Reviews conducted to date suggest that equivalent results are obtained using online and offline surveys (Gosling et al, 2004;Roberts, 2006), with the possible exception of measures that may be subject to social desirability response sets (Roberts, 2006). For example, based on a 10 year longitudinal study of 63,000 student responses to SETs, Risquez, Vaughan, and Murphy (2014) reported that after controlling for class size, faculty, year of evaluation, years of teaching experience and student performance, the effect of administration mode on SET results is minimal. Further, reviewing metaanalyses of non-response bias studies, Peytchev (2013) noted that there is little evidence of a relationship between response rate and non-response bias.…”
Section: Data Qualitymentioning
confidence: 99%
“…Reviews conducted to date suggest that equivalent results are obtained using online and offline surveys (Gosling et al, 2004;Roberts, 2006), with the possible exception of measures that may be subject to social desirability response sets (Roberts, 2006). For example, based on a 10 year longitudinal study of 63,000 student responses to SETs, Risquez, Vaughan, and Murphy (2014) reported that after controlling for class size, faculty, year of evaluation, years of teaching experience and student performance, the effect of administration mode on SET results is minimal. Further, reviewing metaanalyses of non-response bias studies, Peytchev (2013) noted that there is little evidence of a relationship between response rate and non-response bias.…”
Section: Data Qualitymentioning
confidence: 99%
“…Tercero, este trabajo potencia la evaluación docente basada en cuestionarios, dado que a partir de los constructos elicitados será factible especificar instrumentos de evaluación docente, pero reconociendo que los estudiantes usan sus propios constructos para entender e interpretar eventos que suceden a su alrededor y que estos constructos están moderados por sus experiencias individuales. Cuarto, si bien RepGrid fortalece el método de los cuestionarios en el proceso de la evaluación docente, su efectividad final está determinada por su utilización en conjunto con otros métodos de evaluación del desempeño (Risquez, Vaughan, y Murphy, 2015). Por ejemplo, evaluación de pares y portafolios de evidencias (Alderman, Towers, y Bannah, 2012).…”
Section: Conclusionesunclassified
“…The cost of printing, administering and processing the survey results were the most compelling reasons. The time savings in terms of administration and processing of feedback was also key [1]. The time savings related to students too because they would have some time in their own time to reflect on their answers before they submit [9].…”
Section: Am Not Sure Lecturers Were Involved In Any Way In This Newmentioning
confidence: 99%
“…Despite the limitations of high financial cost, waste of time and problems with analysis the paper-based evaluations are widespread [4], [5] in developing countries. As a result, many HEIs in developing countries are migrating to online evaluations where students use online forms [1], [4]. A lot of studies on the course and lecturer evaluation in HEIs [6]- [8] have largely been quantitative with less qualitative studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation